(untitled) (PIONIR: JURNAL PENDIDIKAN, 2021)
The process of transforming knowledge to students in learning there are several ways, one of which is using supporting media. Various supporting media will attract the attention of students. The learning process using media is still rarely carried out in the school environment, causing students to feel bored when studying and having an impact on student learning outcomes. Teachers as educators should think about varied media to increase students’ interest in participating in learning. One of the interesting media to use in learning is Pop Up Book media. This study aims to determine the increase in student learning outcomes through the media Pop Up Book. This research is a Classroom Action Research (CAR). The subjects in this study were 16 students of class VA MIN 4 Aceh Besar. Data collection is done by observation and tests. This observation is used to determine the ability of teachers and students in learning, the data is analyzed by the percentage formula. The result of the research is that the teacher’s activity increased from (69.5%) in the first cycle and in the second cycle to (96%). The activity of students increased from (66.3%) in the first cycle and in the second cycle to (87.5%). And the learning outcomes of students in the first cycle (25%) and in the second cycle increased to (87.5%). Thus, increasing student learning outcomes by using Pop Up Book media can improve student learning outcomes in thematic learning.